2023
DOI: 10.3390/ijerph20075369
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Pain, Chronic Health Conditions and Health Behaviors: Data from the 2016–2018 National Health Interview Survey

Abstract: Spinal pain and chronic health conditions are highly prevalent, burdensome, and costly conditions, both in the United States and globally. Using cross-sectional data from the 2016 through 2018 National Health Interview Survey (n = 26,926), we explored associations between spinal pain and chronic health conditions and investigated the influence that a set of confounders may have on the associations between spinal pain and chronic health conditions. Variance estimation method was used to compute weighted descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…With a lifetime prevalence rate estimated at 70% (Ramanathan et al., 2018 ; Rundell et al., 2017 ; Williams et al., 2018 ), spinal pain has been closely linked with several comorbidities impacting quality of life (de Luca et al., 2023 ; Whitlock et al., 2017 ). Even though we were unable to explore this directly in this study, this association is likely attributed to the disability linked to spinal pain predisposing patients to a more sedentary lifestyle—a primary risk factor contributing to a rise in chronic ill health in later life (Thompson, 2020 ; Wang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a lifetime prevalence rate estimated at 70% (Ramanathan et al., 2018 ; Rundell et al., 2017 ; Williams et al., 2018 ), spinal pain has been closely linked with several comorbidities impacting quality of life (de Luca et al., 2023 ; Whitlock et al., 2017 ). Even though we were unable to explore this directly in this study, this association is likely attributed to the disability linked to spinal pain predisposing patients to a more sedentary lifestyle—a primary risk factor contributing to a rise in chronic ill health in later life (Thompson, 2020 ; Wang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 Global Burden of Disease study underscored SP as a paramount contributor to disability globally, especially affecting individuals aged 25–64 ( GBD 2015 Disease and Injury Incidence and Prevalence Collaborators, 2016 ). Consequently, healthcare costs for SP treatment soared, reaching an estimated $134.5 billion in the United States in 2020 ( de Luca et al, 2023 ). The pressing need for effective prevention and treatment strategies for SP is a critical concern in the realm of global public health.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options for chronic spine pain after injuries in adolescence followed by multiple decades of suffering prior to successful treatment are not found in the medical literature [ 3 , 4 ]. Due to the near impossible design of such long-term investigations, there are no four-decade or longer studies, randomized controlled clinical trails (RCTs), or others that could be found in patients injured in their early teen years and who suffer from spine pain, loss of range of motion (ROM) and disability.…”
Section: Introductionmentioning
confidence: 99%